John Castillo's 'Awd Isaac'. (5th December 2018) - Robert, Bridge
Abstract: The early chronology of Yorkshire dialect poetry features but few individual works, mainly authored by gentlemen. John Castillo was among the few who were from, and remained within, both the working class and the dialect community. Awd Isaac, published in over 23 different editions and the root of his reputation as a dialect poet, was written around 1823. Initially circulated orally and by hand-written copies, it was first published in pirated editions. Despite accreditation in a critical review in 1833, many subsequent editions failed to name an author, and different spellings of the title (Awd, Aud, Old, Oad etc) have complicated attribution. This article contains a bibliography of editions identified to date, an analysis of dialect orthography as a means of revealing relationships between printers and publishers, and a summary of the critical reception of the author and his poem.